Kajian Respon Masyarakat terhadap Pembangunan Infrastruktur Pengendali Banjir dan Rob di Kota Pekalongan - Putri, Shinta Permana; Yahya, Wisely; Hidayah, Ulul (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
This research aims to identify the community's level of knowledge regarding the flood and tide infrastructure development program constructed by the Government of Pekalongan City. Additionally, it aims to formulate recommendations for future program improvements based on the community's perspective. The research utilized a mixed-method approach. Data were collected through a questionnaire administered to 155 respondents. The sampling technique used is proportionate stratified sampling based on population data and the extent of flood-affected areas. Subsequently, data were gathered through a Forum Group Discussion (FGD) involving community leaders. The study employed descriptive statistics and SWOT analysis. The results showed that a significant portion of the community is aware of some flood and tide control infrastructures built by the Government of Pekalongan City, although not all. The community perceived the infrastructure development as less successful. The community perceived that the current infrastructure development needs to be accelerated, leveled, improved, integrated, and adjusted to the needs of each affected region, involving the community in every stage of the program. The findings suggest that the Government of Pekalongan City needs to optimize the development of flood and tide control infrastructure. Keywords: Flood and Tide, Infrastructure Development, Community Engagement